Metabolic syndrome in adults with autistic traits: associated psychological, behavioral, and biological factors in females and males – a PharmLines initiative - Warreman, E. B.; Nooteboom, L. A.; Leenen, P. J. M.; Geurts, H. M.; Terry, M. B.; Bos, J. H. J.; Hak, E.; Hoek, H. W.; van Rossum, E. F. C.; Vermeiren, R. R. J. M.; Ester, W. A. (Frontiers in Psychiatry, 2023)
Background: While cardiovascular diseases is highly prevalent and an important cause of mortality in autistic adults, knowledge on their increased cardiovascular risk is limited. Hence, this study aimed to investigate psychological, behavioural, and physical factors associated with metabolic syndrome (MetS) in adults with autistic traits. Methods: In total, 17,705 adults from the Lifelines Cohort were included and categorized using Autism Spectrum Quotient-10 sum-scores. The quartiles with highest (HQ-traits-group females: n=2635; males: n=1803) and lowest levels of autistic traits (LQ-traits-group, n=idem) were analysed. Using multivariable logistic regression, the associations between MetS and (self-reported and interviewed) psychological, behavioural, and physically measured factors in these stratified groups were investigated. Results: Among females, MetS was more common in the HQ-traits-group than in the LQ-traits-group (10.0% versus 7.5%, p<0.01), while this was not the case among males (HQ-traits-group 13.8% versus LQ-traits-group 13.1%, p=0.52). In both the female and male HQ-traits-group, the presence of MetS was associated with poorer self-reported health, less daily physical activity, and altered leukocyte counts. Conclusion: These findings underline the relevance of adequate cardiovascular prevention in adults with higher levels of autistic traits. Future research could gain more insight into the relationship between cardiovascular risk and autistic traits in females, and into tailored cardiovascular prevention.